Draft nuclear and complete mitochondrial genome assemblies of the flare-horned markhor (Capra falconeri): genomic resources for conservation and phylogenetics - Javeria Wali; Muhammad Waqas; Azhar Hussain Shah; Inam Ullah; Asif Mir; Zunnan Huang; Amjad Ali (Mammalian Genome, 2026)

Ameliorating CO₂ capture performance of PEI/PES hybrid membranes via integration of zeolitic imidazolate frameworks - Sadia Sagar; Aqib Riaz; Farzana Siddique; Aysha Siddiqa; Mohsin Ali; Mahnoor Asif; Muhammad Waqas Iqbal; Fawad Inam (Journal of Environmental Chemical Engineering, 2025)

Projecting future climate extremes in the glacier-fed upper indus basin using machine learning based downscaling of CMIP6 GCMs - Muhammad Amjad Saleem; Muhammad Shoaib; Sarfraz Hashim; Muhammad Shoaib; Hafiz Umar Farid; Muhammad Ismail; Mubashir Ali Ghaffar; Ahmad Mujtaba; Jinwook Lee; Muhammad Azhar Inam; Arshad Ameen (Theoretical and Applied Climatology, 2025)

Machine learning-based streamflow projections in the upper indus basin under CMIP6 climate scenarios - Muhammad Amjad Saleem; Muhammad Shoaib; Sarfraz Hashim; Muhammad Shoaib; Hafiz Umar Farid; Mubashir Ali Ghaffar; Muhammad Ismail; Arshad Ameen; Jinwook Lee; Muhammad Azhar Inam; Changhyun Jun (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Phycocyanin as a sustainable future resource: A review on recent advancements, fundamental challenges, opportunities and applications - Haider Ali; Rashid Iftikhar; Muhammad Ali Inam; Muhammad Umer Abbas; Sahar Saleem; Faras Ahmad Shahbaz; Humayun Nadeem; Aleena Tahir; M. Momin (Bioresource Technology Reports, 2025)

Microbial transformation: the role of fermentation in advancing nutritional quality and human health - Babar Iqbal; Khulood Fahad Alabbosh; Abdulkareem Raheem; Inam Ullah; Ali Raza Khan; Muhammad Sohail Memon (Archives of Microbiology, 2025)

Molecular modeling to design a multiepitope vaccine against emerging tick-borne Yezo virus and its validation through biophysics techniques - Hassan Ayaz; Muhammad Suleman; Asad Ali Shah; Syed Ainul Abideen; Faisal Ahmad; Muhammad Ali; Sajjad Ahmad; Asia Nawaz; Hanbal Ahmad khan; Inam Hussain; Muhammad Irfan; Yasir Waheed (In Silico Pharmacology, 2025)

Plant Growth Promoting Rhizobacteria Regulated Nutrient Uptake in Quinoa (Chenopodium Quinoa Wild) Under Nutrient-Deficient Conditions Through Solubilizing Insoluble Minerals - Ejaz Rafique; Muhammad Zahid Mumtaz; Lingling Li; Inam Ullah; Talha Ali Chohan; Muhammad Waqar Alam; Adnan Mustafa; Waleed A. A. Alsakkaf; Hayssam M. Ali (Journal of Soil Science and Plant Nutrition, 2025)

Highly efficient phosphate extraction from water using bio-composites of nano zero valent iron supported on orange peel powder (nZVI@OPP): performance evaluation and mechanistic insights - Fahad Nadeem; Muhammad Ali Inam; Rashid Iftikhar; Safi Ullah Gill; Hira Amjad (Environmental Science and Pollution Research, 2025)

Biomitigation of noxious metal ions using engineered lignin-based nanocomposites for sustainable environment - Zaeem Bin Babar; Rashid Iftikhar; Komal Rizwan; Shahid Munir; Mashhood Urfi; Fawad Ashraf; Muhammad Ali Inam; Shahid Iqbal; Muhammad Saad; Sajid Mahmood; Nasser S. Awwad; Hala A. Ibrahium (Journal of Water Process Engineering, 2025)

The comparative transcriptome analysis of two green super rice genotypes with varying tolerance to salt stress - Nageen Zahra; Muhammad Uzair; Imdad Ullah Zaid; Kotb A. Attia; Safeena Inam; Sajid Fiaz; Rizk M. Abdallah; Muhammad Kashif Naeem; Umer Farooq; Nazia Rehman; Ghulam Muhammad Ali; Jianlong Xu; et al. (Molecular Biology Reports, 2024)

Highly efficient adsorptive removal of phosphate using novel perovskite lanthanum ferrite/graphene oxide (LaFeO3-GO) hybrids from water - Jawad Rauf; Muhammad Ali Inam; Rashid Iftikhar; Hira Amjad; Deedar Nabi; Waleed Usmani (Journal of Water Process Engineering, 2024)

Comparative phosphate sorption and recovery potential of mono and bimetallic iron‑lanthanum impregnated biochar derived via co-pyrolysis of sewage sludge and wheat straw: Highly effective phosphatic fertilizer - Iqra Irfan; Muhammad Ali Inam; Rashid Iftikhar (Journal of Water Process Engineering, 2024)

The Influence of Pyrolysis Temperature on the Performance of Cotton Stalk Biochar for Hexavalent Chromium Removal from Wastewater - Usama Khalid; Muhammad Ali Inam (Water, Air, & Soil Pollution, 2024)

Development of ZnO-GO-NiO membrane for removal of lead and cadmium heavy metal ions from wastewater - Arslan Maqbool; Ameen Shahid; Zaib Jahan; Muhammad Bilal Khan Niazi; Muhammad Ali Inam; Ahmed M. Tawfeek; Emadeldin M Kamel; Muhammad Saeed Akhtar (Chemosphere, 2023)

Efficient removal of hexavalent chromium Cr (VI) using magnesium-iron layered double hydroxide supported on orange peel (Mg-Fe LDH@OPP): A synthetic experimental and mechanism studies - Waleed Usmani; Muhammad Ali Inam; Rashid Iftikhar; Iqra Irfan; Rabia Adnan; Muhammad Bilal Khan Niazi; Rizwan Khan; Muhammad Hassan (Journal of Water Process Engineering, 2023)

Synthesis, characterization and antifungal potential of titanium dioxide nanoparticles against fungal disease (Ustilago tritici) of wheat (Triticum aestivum L.) - Nadiyah M. Alabdallah; Muhammad Atif Irshad; Muhammad Rizwan; Rab Nawaz; Aqil Inam; Muhammad Mohsin; Iram Khurshid; Hesham F. Alharby; Atif A. Bamagoos; Shafaqat Ali (Environmental Research, 2023)

Entropy-based grid approach for handling outliers: a case study to environmental monitoring data - Anwar Shah; Bahar Ali; Fazal Wahab; Inam Ullah; Kassian T. T. Amesho; Muhammad Shafiq (Environmental Science and Pollution Research, 2023)

CRISPR/Cas9 editing of wheat Ppd-1 gene homoeologs alters spike architecture and grain morphometric traits - Aliya Errum; Nazia Rehman; Muhammad Uzair; Safeena Inam; Ghulam Muhammad Ali; Muhammad Ramzan Khan (Functional & Integrative Genomics, 2023)

Preliminary Geoheritage Assessment of The Gharam Chashma Granitic Batholith (GCGB), Southern Margin of Asian Plate, NW Pakistan: Multiple Constraints from Field Evidence, Petrology, and Physicomechanical Properties - Abbas Ali Naseem; Muhammad Naveed Anjum; Muhammad Yaseen; Muhammad Ali; Waqar Inam; Syed Haroon Ali; Jawad Ahmad; Anees Ahmad Bangash (Geoheritage, 2023)

Deep learning-based marine big data fusion for ocean environment monitoring: Towards shape optimization and salient objects detection - Sulaiman Khan; Inam Ullah; Farhad Ali; Muhammad Shafiq; Yazeed Yasin Ghadi; Taejoon Kim (Frontiers in Marine Science, 2023)
Objective During the last few years, underwater object detection and marine resource utilization have gained significant attention from researchers and become active research hotspots in underwater image processing and analysis domains. This research study presents a data fusion-based method for underwater salient object detection and ocean environment monitoring by utilizing a deep model. Methodology A hybrid model consists of an upgraded AlexNet with Inception v-4 for salient object detection and ocean environment monitoring. For the categorization of spatial data, AlexNet is utilized, whereas Inception V-4 is employed for temporal data (environment monitoring). Moreover, we used preprocessing techniques before the classification task for underwater image enhancement, segmentation, noise and fog removal, restoration, and color constancy. Conclusion The Real-Time Underwater Image Enhancement (RUIE) dataset and the Marine Underwater Environment Database (MUED) dataset are used in this research project’s data fusion and experimental activities, respectively. Root mean square error (RMSE), computing usage, and accuracy are used to construct the model’s simulation results. The suggested model’s relevance form optimization and conspicuous item prediction issues in the seas is illustrated by the greatest accuracy of 95.7% and low RMSE value of 49 when compared to other baseline models.

Do technology and structural changes favour environment in Malaysia: an ARDL-based evidence for environmental Kuznets curve - Wajahat Ali; Inam Ur Rahman; Muhammad Zahid; Muhammad Anees Khan; Tafazal Kumail (Environment, Development and Sustainability, 2020)

Homotypic Clusters of Transcription Factor Binding Sites in the First Large Intron of AGL24 MADS-Box Transcription Factor Are Recruited in the Enhancement of Floral Expression - Tajammul Hussain; Nazia Rehman; Safeena Inam; Wajya Ajmal; Amber Afroz; Aish Muhammad; Yusuf Zafar; Ghulam Muhammad Ali; Muhammad Ramzan Khan (Plant Molecular Biology Reporter, 2019)